2017
DOI: 10.1093/ntr/ntx008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Nicotine Dependence and Addiction Among Young Adults Who Smoke Cigarillos: A Qualitative Study

Abstract: The increasing use of cigarillos among young adults has significant public health consequences. Addressing this issue requires accurate measurement and effective treatment of dependence on cigarillo products. The results of this study directly inform the development of a revised measure of ND, and can contribute to the efficacy of cessation interventions for cigarillo users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Our findings corroborate the findings from existing literature that suggest that when assessing cigar use, more detailed information, such as brand names, is needed. 2,4,7,28,31,33-36 Our findings also expand previous research by suggesting that when assessing cigar use, the use of cigars without manipulation or the use of cigars by manipulating them into blunts should be considered.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings corroborate the findings from existing literature that suggest that when assessing cigar use, more detailed information, such as brand names, is needed. 2,4,7,28,31,33-36 Our findings also expand previous research by suggesting that when assessing cigar use, the use of cigars without manipulation or the use of cigars by manipulating them into blunts should be considered.…”
Section: Discussionsupporting
confidence: 82%
“…Blunt use is different from other tobacco and marijuana use in that the ritual of creating blunts and smoking blunts often occurs in a group activity. 28,30 Thus, it is not surprising that most youth reported that their first experience with blunts and their primary source of information regarding learning how to create and smoke blunts was peers. Social sources (eg, older peers, adults) were also a common source for acquiring cigars among underage youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like others,16 18 we found sharing to be common among cigarillo users. The conventional method yielded higher estimates of daily cigarillo consumption than the detailed method for those who always share products.…”
Section: Discussionsupporting
confidence: 79%
“…Although there is no gold standard, a widely used conventional measure of tobacco consumption relies on two global questions to assess smoking days and number of tobacco products smoked on smoking days 10 11. A growing body of evidence suggests that measurement of cigarillo use may be complicated by several issues, such as variations in product terminology,12 13 manipulation of cigarillos to include marijuana14 15 and sharing of cigarillos in a group setting 16–18. While recent research has addressed some of these issues, such as using brand-specific examples and assessing subtypes of cigar products,13 19 20 to date, none have incorporated cigarillo use patterns into a measurement strategy.…”
Section: Introductionmentioning
confidence: 99%